Sustainability - Cohen, Maurie J, ....- (Medford : Polity Press, 2020)
"Authoritative introduction to one of the most important challenges of the 21st century"--
Sustainability is one of the buzzwords of our times and a key imperative for economic growth, technological development, social equity, and environmental quality. But what does it really mean and how is it being implemented around the world? In this clear-eyed book, Maurie Cohen introduces students to the concept of sustainability, tracing its history and application from local land-use practices, construction techniques and reorientation of business models to national and global institutions seeking to foster sustainable practices. Examining sustainable development in scientific, technological, social and political terms, he shows that it remains an elusive concept and evidence of its unambiguous achievements can be difficult to ascertain. Moreover, developed and developing countries have formulated divergent agendas to engage the notion of sustainability, further complicating its application and progress across the world. Innovative and readily accessible to students from a range of disciplines, this primer takes us on a journey to show that sustainability is as much about unchartered waters as it is about formulating answers to urgent global issues.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Duurzaamheid; Duurzame economie; Environmental engineering; Social change; Sustainable development